Comparison of thyroid profile in premenopausal and postmenopausal women: A case control study - Chandrashekhar G.S (International Journal of Medical Research and Review, 2018)
Introduction : After menopause, diminishedgonadal hormones are found to influence thyroid status. There are a few published literature in this area, to the best of our knowledge. Aim of the study was to compare thyroid profile of postmenopausal women with those in reproductive age group as well as to find the correlation between age and thyroid profile. compare thyroid profiles of young men with those in geriatric age group iii. find if anygender differences in thyroid profiles.Methods: In a case control study, thyroid profiles of 76 post menopausal women and 131 women in reproductive age group were compared. Thyroid profile of 78 young men was compared with that of 24 men in geriatric age group. Genderdifferencesin thyroid profile were studied by comparing thyroid profiles of 207women and 102 men. Statistical analysis was carried out using MannWhitney U test and Linear regression analysis.Results: A significantly higher TSH levels (P<0.05) and decreased T3 (P<0.0001) were observed in postmenopausal women compared to the controls. There was no statistically significant difference in thyroid profiles among men in geriatric age group and young men. There was a significant elevation of TSH in women compared to men (P<0.05). A negative correlation between age and T3 levels was observed in women.Conclusion: Subclinical hypothyroidism was observed in post menopausal women in our setting. A higher tendency of women having subclinical hypothyroidism compared to men was also observed. This suggestsa necessity to assess functional status of thyroid gland periodically in the post menopausal period.